Investigating Barriers to Wireless Field-Level Communication - Rahnamayiezekavat, Payam; Bernold, L. (2013)
Construction projects are information intensive making conventional paper-based information flow a major hindrance to improve productivity in construction. Being risk-averse and resistance to change, the Construction industry hesitates to apply new and untested technology. Most importantly, a contractor needs to know the optimal configuration of such a communication network and, even more importantly, its benefits to project. This paper presents an approach to include risk attitude in calculating a tool’s utility index. Results show that economical concerns including initial investment and operation costs ranked first and second important issues in selecting work-front information delivery method. After money which is somehow a managerial struggle, “ease of use” is the most influential parameter. Furthermore “ease of use” covers operators and labours’ demands and perspectives. Calculated paper-based communication method’s utility factor with a risk neutral point of view was 62 while obtained IT-based utility factor in a risk-averse perspective was 26. Results imply the inertia in switching from customary paper-based approach to state-of-the-art IT based fashion. Introducing inexpensive, maintenance free, user-friendly, IT-based alternatives can revolutionize inefficient state-of-practice.